Unveiling new fungal discoveries in Yunnan Province, China - Jayasiri, Subashini Chathumini; Tibpromma, Saowaluck; Xu, Ruifang; Bhat, Darbhe Jayarama; Elgorban, Abdallah M.; Karunarathna, Samantha C.; Rampelotto, Pabulo H.; Han, Meiyan; Xu, Jianchu (Phytotaxa, 2024)
Fungal taxa can be found almost anywhere and China is recognized as one of the most diverse regions globally. Within Asia, China leads major fungal hotspot studies, with Yunnan Province noted for its high plant and fungal diversity compared to other regions in the country. The Kunming Institute of Botany (KIB), Chinese Academy of Sciences (CAS), is a leading research institute with a botanical garden focused on the taxonomy and phylogeny of plants, fungi, lichen, and related projects. This study introduces new and known taxa from KIB collections based on comprehensive morphological and molecular analyses. Detailed morphological descriptions, illustrations and multigene phylogenetic analyses were used to identify four taxa within the class Dothideomycetes (Pleosporales). This includes a new genus (Paracrassiperidium), a new species (P. fusiforme), and two previously known species (Chaetopyrena penicillata and Pseudokeissleriella bambusicola). The new genus is characterized by dome-shaped, semi-immersed to immersed ascomata with a thick-walled peridium, a hamathecium composed of branched pseudoparaphyses, cylindrical to cylindric-clavate pedicellate asci with a well-developed ocular chamber, and fusiform, hyaline to light brown, septate ascospores.